THE ADJUSTMENT OF NON-TAXABLE INCOME IN INDONESIA: ECONOMIC AND POLITICAL FEASIBILITY - Nur Arif Nugraha (Politeknik Keuangan Negara STAN, 2017)
ABSTRAK Indonesian government has an extensive experience in the adjustment of non-taxable income. Indonesian government decision to adjust non-taxable income has several impacts for Indonesian citizen. The adjustment is to increase an amount of non-taxable income. The most current policy of non-taxable income adjustment is effective from 1 January 2016. Therefore, there are some positive impacts and negative impacts. In one hand, an increase of non-taxable income has an impact to increase the purchasing power of people. On the other hand, this policy has an effect on income tax revenue for the country. This paper will focus on an increase of non-taxable income from the economic feasibility point of view. The first part will explain the policy problem within the implementation. The second part will elaborate an increase of non-taxable income from the economic feasibility point of view. The final part will give a recommendation for Indonesian government about the policy implementation.